Revisiting Axiological Aspects of the Doll Phenomenon Under the Conditions of Cultural Paradigm Change - Maria K. Suvorova; Tatyana N. Adametskaya; Svetlana F. Rashitova (Publishing house "Sreda", 2020)
This article analyzes the phenomenon of dolls in the process of transition from the traditional type of society to the postindustrial one. The authors outline that being a kind of mirror of the era, the doll phenomenon is inextricably linked with cultural norms and values, all social experience, which determined the stability and continuity of various activities. It is also noted that in the process of historical development, the image of the doll undergoes transformation, as does the image of the person himself. The inclusion by the authors the axiological characteristics of the doll phenomenon in the worldview coordinates of cosmo- and anthropocentrism makes it possible to reveal their new quality. The consideration of the doll as a phenomenon from this methodological position opens up new possibilities in understanding the existential essence of man himself. The purpose of the article is to analyze one of the most relevant aspects of the doll phenomenon in modern conditions - a qualitative change in its axiological content and significance in culture. Research methods: historical-comparative and semiotic. The result of the study is the identification of significant changes in the role of dolls in modern culture. It is emphasized that the value orientations of secular society and a desacralized, materialistic worldview result in dehumanization and objectification of the person himself with a pronounced desire to revitalize and humanize the doll. The development of anthropocentric attitudes has reached its limits, as evidenced by the shift in the semantics of dolls into the field of purely formal, external relations and meanings.